Ipomoea triloba Linn-a New Record for Uttar Pradesh from Dehra Dun - Deva, Som; Naithani, H. B. (Indian Forester, 1990)
Ipomoea triloba Linn. A native of tropical America is now reported for the first time for Uttar Pradesh from Debra Dun.